PERKEMBANGAN SEL SPERMATOGENIK MENCIT (Mus musculus L.) SETELAH PEMBERIAN EKSTRAK KULIT KAYU DURIAN (Durio zibethinus Murr.) - Anni Nurliani; Rusmiati; Heri Budi Santoso (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2005)
It has been conducted a study of identify population of spermatogenic cells of mice after induction Durian (Durio zibethinus Murr.) bark extract. This research used completely randomized design with five treatments i.e. control without treatment; control with aquadest; 5% durian bark extract; 10%; and 20% with five repetitions for each treatment. Extract was given per oral in volume dose of 0,5 ml/ 25–30 g/BW per day during 36 days. The result of this study showed that durian bark extracts caused significantly decrease of population of spermatogenic cells in concentrate 5%, 10%, and 20%.